Macroprocess 08 Integrated Project Management - Organizational Design Division (Carlos Figueroa Picado, 2020)
The Macroprocess 08 Integrated Project Management aims to “Ensure the effective management of technical cooperation and organizational development projects at the regional, multinational, and national levels and at Headquarters in their various stages, assisting in the recruitment and articulation of the required internal and external resources”.